2010
DOI: 10.1176/appi.ajp.2010.09121797
|View full text |Cite
|
Sign up to set email alerts
|

Social Norm Processing in Adult Social Phobia: Atypically Increased Ventromedial Frontal Cortex Responsiveness to Unintentional (Embarrassing) Transgressions

Abstract: Objective Generalized social phobia (GSP) is defined by a persistent fear of social disapproval. However, the neural underpinnings of this increased fear and its mediating factors are unclear. Using event-related fMRI, we examined whether the intent of an event, which mediates the neural response to social disapproval in healthy individuals, differentially affects response in GSP. Specifically, would patients with GSP show particularly increased response to embarrassing, unintentional transgressions? Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 37 publications
10
72
0
1
Order By: Relevance
“…Previous work has shown that this population shows heightened medial frontal cortical responses to self-relevant material (Blair et al . 2008 a , 2010, 2011 b ; Goldin & Gross, 2010). Moreover, self-referential processing has been shown to recruit the cortical midline structure from ventromedial and rostral regions to the posterior cingulate cortex (Amodio & Frith, 2006; Northoff et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that this population shows heightened medial frontal cortical responses to self-relevant material (Blair et al . 2008 a , 2010, 2011 b ; Goldin & Gross, 2010). Moreover, self-referential processing has been shown to recruit the cortical midline structure from ventromedial and rostral regions to the posterior cingulate cortex (Amodio & Frith, 2006; Northoff et al .…”
Section: Discussionmentioning
confidence: 99%
“…While these paradigms investigated several aspects of norm processing, the focus of the Social Norm Processing Task (SNPT), originally developed and described by Berthoz et al [17,18] and used in a subsequent study [19], is on the effect of intention on the judgment of social norm violations. The concept of ‘intentionality’ has been extensively studied [20–22] and the effect of the actor’s intention on the evaluation of an action has been shown previously (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the elegant simplicity of static facial expressions, there has been a growing emphasis on other types of stimuli with putatively greater ecological validity such as imagining feared social situations (Blair et al, 2010; Boehme et al, 2014; Nakao et al, 2011), anticipation of public speaking (Boehme et al, 2013; Cremers et al, 2015), performance evaluation (Gimenez et al, 2012; Koric et al, 2012; Pujol et al, 2013), and exposure to social criticism (Blair et al, 2008a; Goldin et al, 2009, 2011b; Ziv et al, 2013a). Such paradigms can provide valuable insights into the more complex processes that are typically encountered in SAD.…”
Section: Introductionmentioning
confidence: 99%